การพัฒนากรอบแนวความคิดสมการโครงสร้างสำหรับเศรษฐกิจหมุนเวียนในธุรกิจขนาดกลางและขนาดย่อม - ชุ่มมี, ภัทรพล (Journal of Roi Kaensarn Academi, 2023)
The circular economy for Thailand aims to generate economic growth from a diversified resource base, increasing gross domestic product (GDP) growth in four sectors from 3.4 trillion baht, representing 21 percent, to 4.4 trillion. baht or 24 percent, especially in agriculture and food. It was found that the GDP of the agricultural sector from 1.3 trillion baht to 1.6 trillion baht by increasing the variety of agricultural products. There is a decision support system based on consumer behavior analysis technology. (Ministry of Higher Education, 2021) The objectives of this research were 1) to examine the components of the transition to a circular economy for small and medium enterprises and 2) to analyze the causal relationship of the transition to a circular economy for small and medium enterprises. The quantitative data were collected from 400 small and medium business entrepreneurs in Bangkok and its vicinity. The research tool used in the research was a questionnaire that tested the consistency value between 0.80-1.00. Research statistics contains of factor analysis and path analysis. The results of the confirmatory factor analysis showed that the P-value passed the acceptable level, the CFI, NFI, GFI and AGFI values between 0.98-0.99 passed the specified criteria, which is greater than 0.90, and the RMR, RMSEA values passed the criteria. As for the results of the path analysis, the fit index for measuring consistency passed the criteria. (Chi-square=238.88, df=115, P-value=0.00, RMSEA=0.058) Recommendations to create the mindset of environmental conservation. Use renewable materials in the production process. New product creation to create added value Reduce unnecessary production processes in order not to cause any impact on the environment. Including various steps together to create and design new products to add value.